Diagnostic testing for chest pain in a pediatric emergency department and rates of cardiac disease before and during the COVID-19 pandemic: a retrospective study - Atmanli, Ayhan; Yen, Kenneth; Zhou, Amy Z. (Frontiers in Pediatrics, 2024)
Objectives -Chest pain is a common chief complaint in pediatric emergency departments (EDs)Coronavirus disease-2019 (COVID-19) has been shown to increase the risk of cardiac disease. It remains unclear how COVID-19 changed how pediatric emergency clinicians approach patients presenting with chest pain. The goal of this study was to characterize the diagnostic testing for chest pain in a pediatric ED before and during the COVID-19 pandemic. Methods -This was a retrospective study of children between the ages of 2-17 years presenting to a pediatric ED from 1/1/2018-2/29/2020 (Pre-COVID-19) and 3/1/2020-4/30/2022 (COVID-19) with chest pain. We excluded patients with a previous history of cardiac disease. Results -Of the 10,721 encounters during the study period, 5,692 occurred before and 5,029 during COVID-19. Patient demographics showed minor differences by age, weight, race and ethnicity. ED encounters for chest pain consisted of an average of 18% more imaging studies during COVID-19, including 14% more EKGs and 11% more chest Xrays, with no difference in the number of echocardiograms. Compared to Pre-COVID-19, 100% more diagnostic tests were ordered during COVID-19, including cardiac markers Troponin I (p<0.001) and BNP (p<0.001). During COVID-19, 1.1% of patients had a cardiac etiology of chest pain compared with 0.7% before COVID-19 (p=0.03).Conclusions -During COVID-19, pediatric patients with chest pain underwent more diagnostic testing compared to Pre-COVID-19. This may be due to higher patient acuity,